2002
DOI: 10.1128/jcm.40.1.123-127.2002
|View full text |Cite
|
Sign up to set email alerts
|

βlasEN: Microdilution Panel for Identifying β-Lactamases Present in Isolates of Enterobacteriaceae

Abstract: A dried investigational use-only microdilution panel named ␤lasEN (a short named derived from the panel's purpose, to identify ␤-lactamases in Enterobacteriaceae) containing 10 ␤-lactam drugs with and without ␤-lactamase inhibitors was developed to identify ␤-lactamases among clinical isolates of Escherichia coli, Klebsiella pneumoniae, Klebsiella oxytoca, Citrobacter koseri, Citrobacter freundii group, Enterobacter spp., and Serratia marcescens. The MICs obtained with a collection of 383 organisms containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…In 1988, in an outbreak of infections mainly due to ceftazidime-resistant, ESBL-producing K. pneumoniae in a Massachusetts long-term care facility, ESBLs, which subsequently were proven to be TEM-12 and TEM-26, were detected in the 2 E. cloacae isolates that were available for testing [14]. Sanders et al [15] identified ESBLs in 8 of 110 E. cloacae isolates from cultures obtained from 6 different hospital laboratories across the United States, and D'Agata et al [16] found SHV-3 ESBL in 3 of 69 E. cloacae isolates from surveillance cultures from patients in the surgical intensive care unit in a Boston tertiary care hospital.…”
mentioning
confidence: 97%
“…In 1988, in an outbreak of infections mainly due to ceftazidime-resistant, ESBL-producing K. pneumoniae in a Massachusetts long-term care facility, ESBLs, which subsequently were proven to be TEM-12 and TEM-26, were detected in the 2 E. cloacae isolates that were available for testing [14]. Sanders et al [15] identified ESBLs in 8 of 110 E. cloacae isolates from cultures obtained from 6 different hospital laboratories across the United States, and D'Agata et al [16] found SHV-3 ESBL in 3 of 69 E. cloacae isolates from surveillance cultures from patients in the surgical intensive care unit in a Boston tertiary care hospital.…”
mentioning
confidence: 97%